EFFECTS OF VARYING LEVELS OF UREA SUPPLEMENTATIONS ON HAEMATO-BIOCHEMICAL INDICES OF YANKASA RAMS FED ENSILED CRUSHED GROUNDNUT SHELL, AFRICAN LOCUST BEAN PULP AND POULTRY LITTER - Yakubu, Ahmed Kirfi; Dumbari, M. K.; Mabu, I. M. (FUDMA Journal of Sciences, 2024)
A study was carried out to assess the effects of varying levels of urea supplementations on haemato-biochemical indices of growing Yankasa rams fed ensiled crushed groundnut shell, African locust bean pulp and poultry litter. The study was carried out at Abubakar Tafawa Balewa University Teaching and Research Farm, Bauchi. Twenty (20) growing Yankasa rams were fed five supplemental diets plus a basal diet. A complete randomized design (CRD) was use to allocate the treatment with each treatment replicated four times. Groundnut shell (GNS) and African locust bean pulp (ALBP) were ensiled with poultry litter as basal diet, Maize bran (MB), cotton seed cake (CSC), groundnut cake (GNC), groundnut haulms (GNH) and urea were used as supplements at various proportions. The basal diet and water were offered ad libitum, three hundred grams (300g) of the supplements were offered before the basal diet to each animal first thing in the morning. Blood samples were collected from ten rams (two animals per treatment), the animals were properly restrained and 5mls of blood was collected through the Jugular veins using syringe and needles, to analyse for various parameters. The results showed that Haematological parameters affected were packed cell volume (PCV) and red blood cell (RBC) at (P
Keywords: Groundnut shell; African locust bean pulp; Yankasa ram; Haemato-biochemical indices